Manajemen di Lembaga Pesantren - Zohriah, Anis; Firdaos, Rizal; Maulana, Ahmad Farhan; Ramadhan, Ganang (Peneliti.net, 2025)
This research focuses on the management of Islamic boarding schools as traditional Islamic educational institutions in Indonesia. Islamic boarding schools, which have a long history dating back to the 13th century, play an important role in education and developing national character. This study identifies the unique characteristics of Islamic boarding schools, such as the central role of the kyai, the independence of the students, and the integration between religious education and social life. Against the background of the challenges of modernization and globalization, this research emphasizes the importance of innovation and management transformation in Islamic boarding schools to maintain their relevance and improve the quality of education. This research describes various aspects of Islamic boarding school management, including planning, organizing and leadership. In planning, Islamic boarding schools face the challenge of setting long-term goals that are realistic and measurable, while in organizing, the role of Kyai and Islamic boarding school administrators is key in carrying out managerial functions. Leadership in Islamic boarding schools, especially the role of kyai, is very crucial in influencing and directing students and the Islamic boarding school community. The research results show that the effectiveness of Islamic boarding school management is very dependent on the ability of the kyai and administrators to adapt to changing times without losing the original identity of the Islamic boarding school. This research suggests the need to develop more systematic and data-based management practices to support sustainability and improve the quality of education in Islamic boarding schools. Apart from that, strengthening collaboration between Islamic boarding schools and various stakeholders has also been identified as an important factor in supporting the transformation of Islamic boarding school management in the modern era.